160 Emphysematous Epididymo-Orchitis: Is Imaging Critical in Active Management? Case Report and Literature Review. (28th February 2022) - Ilangovan, S.; Ghazanfar, N.; Chitale, S.
Abstract: We hereby present a case report regarding a rare cause of acute scrotum secondary to emphysematous epididymo-orchitis (EEO), often not diagnosed until it reaches an advanced stage, when it becomes a clinical diagnosis with crepitus palpable in scrotal wall with cellulitis. This case report details a 55-year-old man with poorly controlled diabetes who presented with an acute scrotum that failed to resolve with oral antibiotics in primary care. Following rapid detection of EEO on an early scrotal ultrasound scan, the patient had surgical debridement and a near-total orchidectomy with only a small stump of testis and tunica albuginea left behind. This highlights the importance of timely imaging in diabetic men with an acute scrotum following a high clinical suspicion of testicular abscess and an incidental, rare but significant finding of the complication of EEO, as both but particularly the latter would warrant early surgical intervention to prevent a catastrophic sequela: Fournier's gangrene. This case report also emphasises that as clinicians, we should have a high index of suspicion for local complications and low threshold for intervention in patients with epididymo-orchitis refractory to adequate period of treatment with oral antibiotics (1–2 weeks), particularly in immuno-compromised and poorly controlled diabetics.